(1257) What future contributions can or offer to improve the world understanding of global problems ما هي المساهمات المستقبلية التي يمكن أن تقدم أو تساهم في تحسين فهم العالم للمشاكل العالمية؟ - Elshafei, Alwalid N. (The Institute Of National Planning., 2018)
The process of studying global problems and building models to analyze them is an OR exercise. In this paper we conceptualize the OR approach to this type of problem and characterize some specific approaches which are available and are in operation. We also give the details of one of these approaches with which we have been directly involved.